One dimensional solute transport in homogeneous porous domain - Mat Toridi, Noorellimia (2013)
Analytical solutions are obtained for dispersion of pollutants along groundwater flow in a longitudinal direction through semi-infinite aquifers which is porous. The solute dispersion is considered temporally dependent while the seepage velocity uniform. The dependency of the solute dispersion to time will indicate that the solute dispersion will change in certain times as the groundwater’s parameters change due to monsoon season and in normal season. Analytical solutions are obtained for uniform pulse type input point source. The Laplace transformation technique is employed to get the analytical solutions of the present problem. The solutions obtained predict the time and distance from the location at which an input concentration is introduced at which the pollution concentration becomes harmless.